COVID-19 Sequelae: Long-Term Impairments in Physical Performance - Spychalska, Maria; Spychalski, Jan (Quality in Sport, 2025)
Introduction: Five years ago, the world faced the COVID-19 pandemic. The rapidly spreading disease necessitated extensive research by scientists and physicians on symptom progression, therapeutic options, and, most importantly, complications associated with the infection. Some of the most common post-COVID-19 complications affect the ability to return to physical activity and subsequent physical performance. Although the acute phase of infection tends to present with mild symptoms in physically active individuals, the resulting complications can be far more disruptive, significantly impairing the recovery process and the ability to resume training. Aim of the study: The aim of this study is to review the available literature to analyze potential COVID-19 complications and their impact on physical performance and return to play (RTP). Materials and methods: A comprehensive review of the literature available across reputable databases including PubMed, Scopus, Google Scholar, Embase and Cochrane Library. The study was conducted using a systematic search of keywords, including "COVID-19", “post- COVID”, “return to play”, "myocarditis", "athletes," "long COVID-19", "physical performance", “Fatigue” and “exercise tolerance”. Results and conclusion: Physically active individuals tend to experience a milder acute phase of infection; however, they are also affected by complications resulting from the disease. Cardiovascular and respiratory complications, along with chronic long-COVID syndrome, reduce physical performance and delay the return to peak fitness. It is crucial to reintroduce training gradually and conduct thorough monitoring of the patient's condition, despite the desire for a rapid return to exercise.